2012
DOI: 10.1111/j.1365-2915.2012.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid resistance in Anopheles gambiae s.s. and Anopheles arabiensis in western Kenya: phenotypic, metabolic and target site characterizations of three populations

Abstract: Field and laboratory investigations revealed phenotypic, target site and metabolic resistance to permethrin in an Anopheles gambiae s.s. (Diptera: Culicidae) population in Bungoma District, a region in western Kenya in which malaria is endemic and rates of ownership of insecticide-treated bednets are high. The sensitivity of individual An. gambiae s.l. females as indicated in assays using World Health Organization (WHO) test kits demonstrated reduced mortality in response to permethrin, deltamethrin and bendio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
96
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(126 citation statements)
references
References 39 publications
28
96
1
1
Order By: Relevance
“…gambiae s.s is still the predominant species of the gambiae complex despite several rounds of pyrethroid IRS and increased use of LLINs. The possible selection of supplementary resistance mechanisms in An.gambiae s.s based on enhanced metabolism may explain the high prevalence of resistance and persistence of An.gambiae s.s in our study area, as it has been reported in a different area of Kenya [36], but this has yet to be confirmed.…”
Section: Discussionmentioning
confidence: 61%
“…gambiae s.s is still the predominant species of the gambiae complex despite several rounds of pyrethroid IRS and increased use of LLINs. The possible selection of supplementary resistance mechanisms in An.gambiae s.s based on enhanced metabolism may explain the high prevalence of resistance and persistence of An.gambiae s.s in our study area, as it has been reported in a different area of Kenya [36], but this has yet to be confirmed.…”
Section: Discussionmentioning
confidence: 61%
“…gambiae s.s . populations (Kawada et al ., ; Ochomo et al ., ). Elsewhere in Uganda a few kilometres north of our study area, malaria vectors remain fully susceptible to bendiocarb (Morgan et al ., ; Mawejje et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recent reports confirming the rapid spread of insecticide resistance underline the need for alternative approaches in addition to insecticide-based methods. [7][8][9][10][11][12] In this study, we aimed to quantify the effects of eave screening in combination with a push-pull system that interferes with mosquito host-seeking behavior through the simultaneous release of repellent volatiles from the house eaves to "push" mosquitoes away from the peridomestic space and attractive volatiles released from an odor-baited trap to "pull" mosquitoes toward this alternative, pseudohost and remove them from the environment. Push-pull is a term originally adopted in the context of agricultural pest management.…”
Section: Introductionmentioning
confidence: 99%